2020
DOI: 10.1093/zoolinnean/zlaa116
|View full text |Cite
|
Sign up to set email alerts
|

Diplura in caves: diversity, ecology, evolution and biogeography

Abstract: Diplurans (Hexapoda) are considered the ‘ideal cavernicolous animal’ having one of the highest ratios of cave-adapted vs. non-cave-adapted species. They are successful colonizers of subterranean habitats, thriving in all cryptic, dark, terrestrial environments. Diplurans play an important role in the decomposition of organic matter below the ground and are sensitive to anthropogenic pressures. We present the first comprehensive review about cave Diplura diversity, ecology, evolution, distribution and biogeogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…We showed that the distribution ranges of both soil and cave Eukoenenia species are very narrow even when compared to other subterranean species, and that range size does not significantly differ between the two guilds here considered. This suggests a limited dispersal potential for most species, as also empirically observed for other small‐sized soil‐ and cave‐dwelling specialists, such as proturans (Galli & Rellini, 2020) and diplurans (Sendra et al, 2020). An anecdotal example of this low dispersal ability can be found in the case of Eukoenenia maquinensis and E. sagarana , two cave‐adapted palpigrades from Brazil.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We showed that the distribution ranges of both soil and cave Eukoenenia species are very narrow even when compared to other subterranean species, and that range size does not significantly differ between the two guilds here considered. This suggests a limited dispersal potential for most species, as also empirically observed for other small‐sized soil‐ and cave‐dwelling specialists, such as proturans (Galli & Rellini, 2020) and diplurans (Sendra et al, 2020). An anecdotal example of this low dispersal ability can be found in the case of Eukoenenia maquinensis and E. sagarana , two cave‐adapted palpigrades from Brazil.…”
Section: Discussionsupporting
confidence: 60%
“…This suggests a limited dispersal potential for most species, as also empirically observed for other small-sized soil-and cave-dwelling specialists, such as proturans (Galli & Rellini, 2020) and diplurans (Sendra et al, 2020). An anecdotal example of this low dispersal ability can be found in the case of Eukoenenia maquinensis and E. sagarana, two caveadapted palpigrades from Brazil.…”
Section: Distribution Patterns and Ecologymentioning
confidence: 52%
“…This impediment (also known as 'Linnean shortfall'; Hortal et al, 2015) is especially problematic in studies focusing on community structure and functioning. It is particularly severe for tropical areas, whose subterranean fauna were largely unknown until very recently (e.g., Alvarenga et al, 2021;Trajano & Bichuette, 2010;Trajano et al, 2016), as well as for certain small-sized animal groups which have been traditionally neglected despite being relatively abundant in subterranean habitats, such as diplurans (Sendra, Antić, et al, 2020;Sendra, Palero, et al, 2020), proturans (Galli et al, 2021), palpigrades (Mammola et al, 2021), nematodes (Du Preez et al, 2017), gastrotrichs (Kolicka et al, 2017), and other meiofaunal lineages (Martínez et al, 2019;Sánchez & Martínez, 2019). The lack of taxonomists for many groups surely hampers the conduction of more concise studies on cave communities in many regions; a situation that is further aggravated by the existence of often high cryptic diversity within most subterranean taxa (Delić et al, 2017;Eme et al, 2018;Esposito et al, 2015;Fišer et al, 2018;Gonzalez et al, 2017;Niemiller et al, 2012).…”
Section: Biological Impedimentmentioning
confidence: 99%
“…In caves, diplurans from the families Campodeidae and Japygidae are found in karst and in volcanic formations all around the world, except in extreme cold or dry regions or areas that experienced these extreme conditions in the past (Sendra et al ., 2020b).…”
Section: Ecologymentioning
confidence: 99%
“…All diplurans inhabit soil and subsurface terrestrial habitats, extending from non-consolidated debris in soils to network of voids in the bedrock, including caves (Condé, 1956;Sendra et al, 2020b) (Fig. 3).…”
Section: Ecologymentioning
confidence: 99%